2021
DOI: 10.1186/s40168-020-00962-2
|View full text |Cite
|
Sign up to set email alerts
|

Japanese quail (Coturnix japonica) as a novel model to study the relationship between the avian microbiome and microbial endocrinology-based host-microbe interactions

Abstract: Background Microbial endocrinology, which is the study of neuroendocrine-based interkingdom signaling, provides a causal mechanistic framework for understanding the bi-directional crosstalk between the host and microbiome, especially as regards the effect of stress on health and disease. The importance of the cecal microbiome in avian health is well-recognized, yet little is understood regarding the mechanisms underpinning the avian host-microbiome relationship. Neuroendocrine plasticity of avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
1
11
0
Order By: Relevance
“…CRHR1 is an essential regulator of the HPA axis; its hippocampal expression has also been shown to be reduced by maternal separation in mice 58 and CRHR1 -deficient mice are unable to mount a corticosterone response to stress 59 . Moreover, this reduction in plasma corticosterone levels under basal conditions has previously been described in European starling 60, 61 and in this line of quail subjected to a chronic stress procedure 40 , whereas more acute stress increases corticosterone levels in this species 38 . We found reduced PCNA expression in the hypothalamus of the STRESS-T group, which suggests decreased cell proliferation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…CRHR1 is an essential regulator of the HPA axis; its hippocampal expression has also been shown to be reduced by maternal separation in mice 58 and CRHR1 -deficient mice are unable to mount a corticosterone response to stress 59 . Moreover, this reduction in plasma corticosterone levels under basal conditions has previously been described in European starling 60, 61 and in this line of quail subjected to a chronic stress procedure 40 , whereas more acute stress increases corticosterone levels in this species 38 . We found reduced PCNA expression in the hypothalamus of the STRESS-T group, which suggests decreased cell proliferation.…”
Section: Discussionsupporting
confidence: 71%
“…Japanese quails were used because we have already shown that their anxiety-like behavior and memory properties are impacted by a chronic stress procedure (unpredictable repeated negative stimuli for 21 days) 32,33 and gut microbiota manipulations (germ-free model, microbiota transfer and probiotic supplementation) [34][35][36][37] . Moreover, Japanese quail have recently been suggested as a relevant model to study the involvement of gut microbiota in stress processes 38 . Here, the approach of cecal microbiota transfer (CMT) was used involving the transfer of microbiota from a chronically-stressed individual to germ-free naïve quails to investigate whether the CMT induced any negative consequences on quails' spatial and cue-based memory abilities as previously demonstrated in the stressed donors 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our observed association of Lactobacillus with fear behavior, we observed that Clostridiales were enriched in the low fear fowl and several unknown Clostridiales species have been associated with reduced stress in Japanese quail. [ 40 ] This observation is interesting in light of previous findings associating these taxa with impaired fear memory in obese mice, including members of the orders Lachnospiraceae and Ruminococcaceae . [ 41 ] Clostridiales are also known to promote host serotonin biosynthesis [ 42 ] and higher blood serotonin has been observed in the low fear red junglefowl males.…”
Section: Discussionmentioning
confidence: 82%
“…As described previously, the avian gut microbiota along with their genes and gene products (the microbiome), perform several functions that heavily impact host physiology. Not only does the gut microbiome play a critical role in modulating host immune defense ( Kogut et al, 2017 ; Broom and Kogut, 2018 ), brain function ( Villageliu and Lyte, 2018 ; Lyte et al, 2021 ), host metabolism regulation ( Stanley et al, 2014 ; Lyte et al, 2021 ; Zhang et al, 2021 ), but also other physiological processes and characteristics thought to depend solely on the genetic program of the bird; gut-liver axis ( Bao et al, 2021 ), gut-bone axis ( Wideman et al., 2012 ; Tomaszewska et al, 2015 ; Airubaye et al, 2020 ), and gut-muscle axis ( Zhang et al, 2021 ). A greater understanding of the key signaling pathways of the cross-species homeostatic regulation between the gut microbiota and its host implicated in these axes are a prerequisite for optimizing therapeutic dietary strategies to manipulate the gut microbiota.…”
Section: New Conceptsmentioning
confidence: 99%